Fabrication and characterization of waste eggshell microparticles reinforced biodegradable composite packaging films enriched with pectin and orange peel essential oil - Radia Iffath; Rowshon Ara; Tanvir Ahmed; Abonti Biswas (Applied Food Research)
Transforming waste materials into valuable commodities is a promising strategy to alleviate challenges associated with managing solid waste, benefiting both the environment and human well-being. This study is focused towards harnessing the potential of waste eggshell microparticles (ESMP) (0.10, 0.15, 0.20 g/150 mL) as reinforcing biofiller and orange peel essential oil (OPEO) (14 %, 25 % and 36 %, w/w) as bioactive agent with pectin (2.80, 2.85, 2.90, and 3.00 g/150 mL) to fabricate five different biocomposite films using particle dispersion and solvent casting technique. The addition of ESMP and OPEO progressively increased film thickness and led to variations in transparency. Micromorphological analysis and vibrational spectroscopy indicated hydrophobicity and compactness, as showed by the loss of free O − H bonds, sharpening of aliphatic C − H and stretching of C = C, C − O and C − O − C bonds with increasing filler content. Noticeable improvements in thermal stability and tensile strength were observed, while the flexibility was minimized. The films displayed remarkable barrier properties against hydrological stress, as evidenced by a reduction in water activity, moisture content, water uptake capacity, and solubility. The antioxidant activity against DPPH radicals suggested efficient release of bioactive compounds. Antibacterial assessment revealed inhibitory effect on Staphylococcus aureus and Bacillus cereus. During soil burial, notable weight loss along with shrinkage confirmed the film biodegradability. In conclusion, the pectin-ESMP-OPEO biocomposite films show potential characteristics as food packaging materials, warranting further performance testing on food samples.